ANNE J. GILLILAND, SUE McKEMMISH, and ANDREW J. LAU, eds., Research in the Archival Multiverse - Sheffield, Rebecka (Archivaria, 2017)
Research in the Archival Multiverse. ANNE J. GILLILAND, SUE McKEMMISH, and ANDREW J. LAU, eds. Clayton, VIC: Monash University Publishing, 2017. viii, 1,064 pp. ISBN 978-1-876924-67-6